Spectrum of Radiological Findings in Hysterosalpingography for Female Subfertility: A Retrospective Cross-Sectional Study in a Tertiary Care Center of Nepal - Khanal, Umesh; Katwal, Shailendra; Shrestha, Sunita; Shah, Ram Swarth (Nepalese Journal of Radiology, 2023)
Introduction: Hysterosalpingography (HSG) is a commonly used diagnostic procedure to investigate the causes of female subfertility. This study aimed to evaluate the range of findings observed in HSG examinations conducted for this purpose. Methods: A prospective cross-sectional study was conducted at the Department of Radiology and Imaging, Tribhuvan University Teaching Hospital, from December 2022 to April 2023. The study included 196 female participants who underwent HSG and met the inclusion criteria. Results: Out of the 196 participants, 127 (64.8%) were categorized as having primary subfertility, while 69 (35.2%) had secondary subfertility. The mean age of the participants was 30.61±5.623 years, with an age range of 20 to 45 years. Among the participants, 142 (72.4%) exhibited a normal uterus, 23 (11.7%) displayed left tubal occlusion, 17 (8.7%) showed right tubal occlusion, 13 (6.6%) had other findings, and 1 (0.5%) was diagnosed with uterine fibroids. Conclusions: This study demonstrated that approximately one out of every five HSG examinations performed to evaluate subfertility revealed tubal occlusion. Consequently, the high detection rate of uterine and tubal pathologies using HSG underscores its critical role as a diagnostic tool for assessing women with subfertility.